Heat-actuated valve implementation in a point-of-care, paper-based microfluidic device for infectious disease detection - Kevin P. Jiang; Steven Bennett; Paul Yager (PLoS ONE, 2026)
Paper-based microfluid devices have great potential to perform complex assays like nucleic acid amplification tests (NAATs) in point-of-care (POC) and low resource settings, but have not often succeeded because there is frequently need for affordable and simple solutions to address complex fluidics and sample delivery without risk of contamination. These issues are exacerbated when multiple sample processing procedures must be automated by valve integration in the absence of advanced supportive instrumentation or trained personnel. For NAAT application in remote or home environments, valving within a POC device must facilitate precise fluidic movement and physically separate each chemical processing step. Ideally, the valve should also be affordable, easy to manufacture, robust in varying climate environments, reliable when stored under ambient conditions, affordable, and non-reactive with chemical reagents or samples. Here, we report the design and integration of two adaptable thermally-actuated valves for application in a point-of-care, paper-based rapid analysis device. Both valves are designed to facilitate the fluidic movement and control necessary to enable reverse-transcriptase loop-mediated isothermal amplification (RT-LAMP) reactions in a paper-based device. Each valve could be used independently or alongside the other valve to control fluidic movement at specific locations along the paper fluidic pathway. The valves differ in their material composition, fabrication, and mechanisms for fluidic control, but both are affordable, durable, and simple to use. We demonstrated that each valve could be used to enable RT-LAMP reactions in a paper-based device for detecting either RNA or DNA biomarkers for respiratory infectious diseases (COVID and Flu A) from human nasal swabs.